A willing murder - Deveraux, Jude (Deveraux, Jude. Medlar mystery, 2018)
After two bodies are found in a quiet Florida community, old secrets and deadly grudges are exposed, prompting retired novelist Sara Medlar, her niece Kate, and long-term houseguest Jackson to team up to try to unmask the killer.